Clinical T Cell Receptor Repertoire Deep Sequencing and Analysis: An Application to Monitor Immune Reconstitution Following Cord Blood Transplantation - Gkazi, Athina Soragia; Margetts, Ben K; Attenborough, Teresa; Mhaldien, Lana; Standing, Joseph F.; Oakes, Theres; Heather, James M.; Booth, John; Pasquet, Marlene; Chiesa, Robert; Veys, Paul; Klein, Nigel; et al. (Frontiers in Immunology, 2018)
Spectratyping assays are routinely used to assess the T cell receptor (TCR) repertoire in haematopoietic stem cell transplant (HSCT) recipients. This is used as a surrogate monitoring procedure to identify the quality of T cell immune reconstitution following treatment. However, whilst useful, there are significant limitations with TCR spectratyping, notably the inability to provide any information on the clonotypes present. Greater detail on the TCR clones present would be clinically relevant in the context of immune reconstitution following HSCT, especially with regards to graft versus host disease (GvHD) and viral reactivations. In this study we developed and applied a Next Generation Sequencing (NGS) approach to assess the TCR repertoire in post cord blood transplant (CBT) patients. We utilised a CDR3 next generation sequencing (NGS) approach to obtain comprehensive TCR data on 16 post CBT patients from Great Ormond Street Hospital (GOSH) and 5 control cord samples. These were analysed to provide a quantitative measurement of the TCR repertoire and its constituents in patients post CBT. We were able to both recreate and quantify inferences typically drawn from spectratyping data. Additionally, we demonstrate that a NGS approach to TCR assessment can provide novel insights into the recovery of the immune system following CBT. We demonstrate that NGS can be used to accurately quantify TCR repertoire diversity and to provide valuable additional information on the numbers and sequences of the clonotypes present. We serially assessed progress of T cell immune reconstitution post-transplant demonstrating that there is dramatic variation in TCR diversity early post CBT and that the dynamics of T cell immune reconstitution is perturbed by the presence of GvHD. It may also be possible to use NGS TCR analysis to link certain clonotypes to specific antigens. However, we urge caution with interpretation of the data in this manner since we also show the presence of HIV-1 ‘specific’ and clonally expanded sequences in clinically verified HIV seronegative CBT patient samples.